Bridging cultures: An evaluation of the Chinese translation of O. Henry’s “The Last Leaf” - Ei Khine Zune; Yang Li; Zin Nandar Win (Researcher and Lecturer Society, 2025)
The study examines the difficulty of effectively translating the stylistic and cultural subtleties of O. Henry’s “The Last Leaf” into Chinese, considering the language and cultural differences between English and Chinese. This study seeks to examine the translation strategies employed by Huang Yuan Shen in the Chinese version of “The Last Leaf” utilizing Bell’s framework, determining the prevalence and efficacy of each strategy. A line-by-line qualitative and quantitative comparison analysis was performed between the English source text and the Chinese target text, utilizing Bell’s nine translation strategies as the coding framework. The study revealed that all nine tactics were utilized, with domestication (32.7%) being the most prevalent and speech act alteration (3.32%) the least adopted, hence improving the clarity, appeal, and cultural accessibility of the translation. These findings emphasize the significance of strategy selection in literary translation, illustrating how the proper use of domestication and other approaches can maintain narrative intent while aligning with the cultural context of the target audience.